IN AGGRESSIVE ENVIRONMENTS SALT RESISTANCE OF CONCRETE WITH CHEMICAL ADDITIVES - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdug‘ofurovich (Journals Park Publishing, 2022)
The article presents data from experimental studies of the effect of polymer additives POLY – ANS on capillary absorption of concrete. It is shown that under the influence of POLY– ANS additives, the density, water tightness of concrete increases and hydrophobization of the walls of pores and capillaries is ensured (the wettability of concrete decreases). It was found that for accelerated assessment of the degree of influence of POLY – ANS additives on the permeability of concrete, it is effective to use the criterion of a relative measure of hydrophobicity.
Keywords: capillary absorption, saline solutions, POLY – ANS polymer additive, pore hydrophobization, permeability, criterion of relative measure of hydrophobicity.